Expansion of Paddy Farming in the Northeast Region of China and Its Impact on the Local Environment: Case Studies of Baicheng and Da’an Cities, Jilin Province - Ma, Jian (WILAYAH: The International Journal of East Asian Studies, 2015)
China is the most populous country in the world, and ensuring food security for a huge and growing population is the largest issue for the Chinese government. In northern China, especially in arid and semi-arid regions, poor natural environment, signified by a high degree of soil salinization, a large number of saline and alkaline land not only hinders the increase of food production but also promotion of farmers’ income. This has impeded regional sustainable development. In order to ameliorate the saline-alkali land, improve the ecological environment, increase rice output and promote farmers’ income, China has carried out projects of saline-alkali land amelioration by planting paddy in the northeast semi-arid region since the 1980s. Results show that rice cultivation is a very effective way to ameliorating the saline-alkali land, and it can increase the rice while promoting income of farmers. This paper analyzes the cost and benefits of growing rice and examines the impact of paddy farming on the local environment.